Error-resilient transmission of resolution-scalable image and video over wireless channels - Al Muhit, Abdullah; Chuah, Teong Chee (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
A new robust transmission strategy for scalable image and video is proposed. To protect the coded bit-stream according to the channel conditions, the proposed scheme exploits the progressive by resolution' structure of the scalable code-stream and takes into account the unequal importance as well as the effect of channel errors at different resolution levels towards reconstructing the source. A salient feature of the algorithm is its compatibility for multimedia applications requiring multi-resolution transmission to single or multiple clients. Results show that the proposed algorithm enables considerable gains in terms of subjective and objective image qualities over existing approaches.(1)